A comparative analysis of raw and processed Radix Paeoniae Alba samples using HPLC, chemometrics, and antioxidant activity. (13th June 2020) - You, Guangjiao; Li, Chenghao; Mao, Yingying; Ren, Xiaoliang; Liu, Yanan; Wang, Meng
Abstract: Radix Paeoniae Alba (RPA) and its processed products are commonly used in traditional Chinese medicine, but the chaos phenomenon among processed products often occurs. In this study, we used multiple chemometric methods to analyze raw and six different processed products of RPA based on HPLC fingerprinting. Heat map analysis was used to assess the changes in chemical composition. Principal component analysis was used for classification, and the samples were divided into four classes: class 1 (raw, wine‐processed, and vinegar‐processed products), class 2 (bran‐processed and soil‐processed products), class 3 (stir‐fried products), and class 4 (coke products). Further, the orthogonal partial least squares discriminant analysis model was used to obtain chemical markers among different classes. The antioxidant property of RPA is an important factor responsible for its pharmacological effects, and so the antioxidant activity of RPA was also investigated. We measured 2, 2‐diphenyl‐1‐picrylhydrazyl radical (DPPH) and hydroxyl radical scavenging ability, and ferric reducing antioxidant power. The total antioxidant activity follows the order: coke > stir‐fried > soil‐processed > bran‐processed > wine‐processed > raw > vinegar‐processed products. These results suggest that different processing methods affect the chemical composition and antioxidant power of RPA, and thus, different products of RPA should not be mixed.